2022
DOI: 10.1166/jbn.2022.3233
|View full text |Cite
|
Sign up to set email alerts
|

Reactive Oxygen Species-Responsive Polyether Micelle Nanomaterials for Targeted Treatment of Ulcerative Colitis

Abstract: As one of the most challenging inflammatory diseases, the incidence of ulcerative colitis (UC) is increasing year by year, but the existing therapeutic drugs are not effective and lack of targeting. Nanomaterials are expected to become promising delivery system due to their good targeting effects. Here, we designed a nanomaterial sensitive to reactive oxygen species, which can be used to treat IBD, especially UC. It is a self-assembled polyether micelle that can be oxidized at the inflammation site where the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…Among immunomodulatory factors, the inflammatory response is considered a central mechanism in the pathophysiology of UC, and pro-inflammatory cytokines play an active role in the inflammatory response by inducing macrophage migration and the release of inflammatory mediators, which further amplify the inflammatory response (Zhao et al, 2022 ). NF-κB plays a central role in regulating the inflammatory process (Lee et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…Among immunomodulatory factors, the inflammatory response is considered a central mechanism in the pathophysiology of UC, and pro-inflammatory cytokines play an active role in the inflammatory response by inducing macrophage migration and the release of inflammatory mediators, which further amplify the inflammatory response (Zhao et al, 2022 ). NF-κB plays a central role in regulating the inflammatory process (Lee et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…Results of this study showed that the fabricated delivery system significantly repaired the intestinal barriers and the colonic damaged tissues were healed effectively (Zhao et al. 2022 ). Similarly, Haiting et, al.…”
Section: Smart Nanosystem Targeting Ulcerative Colitismentioning
confidence: 97%